2007
DOI: 10.1007/s00299-007-0411-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome doubling in a Rosa rugosa Thunb. hybrid by exposure of in vitro nodes to oryzalin: the effects of node length, oryzalin concentration and exposure time

Abstract: Chromosome doubling was induced in vitro in a diploid hybrid of Rosa rugosa Thunb. using oryzalin as the spindle inhibitor. Nodal sections, 2 mm long, were exposed to 2.5 or 5 microM oryzalin and 10 mm nodal sections were exposed to 5 microM oryzalin for 0 (controls), 6, 12, 24 and 48 h. The ploidy of the emergent shoots was determined by flow cytometry. The frequency of tetraploid and mixoploid leaves that developed from 2 mm nodal sections exposed to 5 microM oryzalin peaked at 12 h exposure, when 35% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 15 publications
3
76
0
1
Order By: Relevance
“…Although, in our daylily tetraploids the stomata, leaves, and flowers were larger, the bud number per scape was lower in both cultivars, and the stem length, depending on cultivar, was similar or lower compared to diploids. Negative correlation associated with tetraploidisation was also noted in Rosa rugosa for the number of flowers per inflorescence (Allum et al 2007) as well as the number of flowers per plant and the stem length in Vicia villosa (Elradi and Unal 2010). Reduction in plant height was noted for some fruit plants such as cherry rootstock (Webster 1996) and citrus hybrid trees (Jaskani and Khan 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although, in our daylily tetraploids the stomata, leaves, and flowers were larger, the bud number per scape was lower in both cultivars, and the stem length, depending on cultivar, was similar or lower compared to diploids. Negative correlation associated with tetraploidisation was also noted in Rosa rugosa for the number of flowers per inflorescence (Allum et al 2007) as well as the number of flowers per plant and the stem length in Vicia villosa (Elradi and Unal 2010). Reduction in plant height was noted for some fruit plants such as cherry rootstock (Webster 1996) and citrus hybrid trees (Jaskani and Khan 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors report that liquid medium could successfully be adopted for multiplication of potato seedlings Fortes, 2003, 2004), banana (de Siqueira et al, 2013), and pineapple (Barboza et al, 2009). Regarding the successful generation of autopolyploid plants, Allum et al (2007) reported that the combination of high antimitotic doses and long exposure times can double the DNA content, resulting in high ploidy levels and the generation of several mixoploids. Therefore, it is important to evaluate cultivation under different exposure times and antimitotic concentrations of cassava apical and lateral explants because these conditions might vary for each species and type of material used (Pereira et al, 2012).…”
Section: Effect Of Oryzalin Concentration and Exposure Time On Cassavmentioning
confidence: 99%
“…Polyploidy can be induced using antimitotics, such as colchicine and oryzalin (Allum et al, 2007;Ascough and Van Staden, 2008;Rêgo et al, 2011). Colchicine is the most widely used and successful antimitotic (Ishigaki et al, 2009;Quesenberry et al, 2010;Souza-Kaneshima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The bud bursts originated from one or a few cells of the meristematic tissue results in a low frequency of chimeric plant regeneration since the exposure time as well as type and concentration of the antimitotic substance used for chromosome duplication was previously adjusted (LATADO et al, 2007). In addition, ALLUM et al (2007) reported that oryzalin diffuses better into the meristematic tissue through the cut (which was made in the explant during micropropagation) than through the epidermis or cuticle (which seems to prevent the substance from entering). This may have favored polyploidization via tissue culture.…”
Section: Chromosome Duplicationmentioning
confidence: 99%
“…This may have favored the occurrence of tetraploidy in the SCM 60 genotype (Table 1). Oryzalin has shown to be effective in the chromosome duplication in roses (ALLUM et al, 2007), and other fruit and ornamental plants (DHOOGHE et al, 2011).…”
Section: Chromosome Duplicationmentioning
confidence: 99%